Stable tearing characterization of three materials with three methods - Johnston, Elizabeth Nicole (Kansas State University, 2012)
Over the past several years the crack tip opening angle (CTOA) has been identified as one of the key fracture parameters to characterize low constraint stable tearing and instability in structural metallic alloys. This document presents the results of experimental stable tearing characterizations. Characterization methods include optical microscopy and marker band measurements of crack front tunneling. Specific attention is given to the measurement methods used, and also the correlation between CTOA and Delta-5. The effect of tunneling and comparisons with computational results are discussed, and the effect of material and measurement method on CTOA is observed and a clear relationship is seen. Preliminary work on future studies into internal features and behavior is also presented.
Keywords: Crack tip opening angle; Stable tearing; Mechanical Engineering (0548)